Study of Γ-hyperrings by fuzzy hyperideals with respect to a t-norm - Naka, Krisanthi; Hila, Kostaq; Onar, Serkan; Ersoy, Bayram Ali (SCIENDO, 2019)
In this paper, we study the Gamma-hyperrings via T-fuzzy hyperideals. By means of the use of a triangular norm T, we define, characterize and study the T-fuzzy left and right hyperideals, T-fuzzy quasi-hyperideal and bi-hyperideal Gamma-hyperrings in and some related properties are investigated. Regular Gamma-hyperrings are characterized in terms of T-fuzzy quasi-hyperideal and T-fuzzy bi-hyperideal. We also introduce the T-(lambda, mu)-fuzzy Gamma-hyperideals in and investigate some of their properties.
Keywords: Gamma-hyperrings; t-norm; T-fuzzy (resp. left, right) hyperideal; T-fuzzy quasi(bi)-hyperideal; ISOMORPHISM THEOREMS; Mathematics